If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2y + 1) = 3(4 + -5y) Reorder the terms: 5(1 + 2y) = 3(4 + -5y) (1 * 5 + 2y * 5) = 3(4 + -5y) (5 + 10y) = 3(4 + -5y) 5 + 10y = (4 * 3 + -5y * 3) 5 + 10y = (12 + -15y) Solving 5 + 10y = 12 + -15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15y' to each side of the equation. 5 + 10y + 15y = 12 + -15y + 15y Combine like terms: 10y + 15y = 25y 5 + 25y = 12 + -15y + 15y Combine like terms: -15y + 15y = 0 5 + 25y = 12 + 0 5 + 25y = 12 Add '-5' to each side of the equation. 5 + -5 + 25y = 12 + -5 Combine like terms: 5 + -5 = 0 0 + 25y = 12 + -5 25y = 12 + -5 Combine like terms: 12 + -5 = 7 25y = 7 Divide each side by '25'. y = 0.28 Simplifying y = 0.28
| 9+-8x=40-15x | | 3(2x-5)=-1 | | 8x-29=3x+1 | | 3x-2=10-3x | | 5+3(-2x+2)=6-4(x+1) | | 9-8x=34x+23 | | 15x-7=9+7x | | 8(9+b)-4b= | | 3r+17-2r+6= | | v^2-16v-20=-5 | | -10=5g | | n^2+16-80=0 | | 10=50e^2(x-1) | | r^2-2=34 | | 4x+24=14-66 | | 2(x+5)=3(10-x) | | X^2+10=4 | | 10x+-6=8x+4 | | 25+2x=37-9x | | 10x-6=8+4 | | -6(4m-1)+7(6m-2)=2m+8m | | 10-6/2+5*7 | | -2(-x+5)=-(6x-1) | | x^5-2x^2+x+11=0 | | 12x+-38=6x+4 | | 88=-8(7k+2)+4k | | -12+4x=5x-11 | | 12x-38=6x-4 | | 3x+36=11x-34 | | 2+4x+x=7 | | 4n^2-11n-29=-5 | | -2(x+1)+5x=3 |